Guidance and Counselling Services as Efforts to Enhance Awareness in Avoiding Cyber Dating Violence Among Young Adults - Khoirunnissa; Solehuddin, Muhammad; Yudha, Eka Sakti (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Currently, cases of violence in dating in cyberspace are increasing along with advances in technology known as cyber dating violence (CDV). Cyber dating violence has an impact on psychological well-being and the ability to develop romantic relationships, thus disrupting the early developmental tasks of adults. Guidance and Counseling play a role in achieving optimal developmental tasks. Guidance and Counseling play a role in achieving optimal developmental tasks, so it is necessary to determine the right services for CDV cases. The purpose of this study was to analyze Guidance and Counseling services that can increase awareness to avoid CDV. This literature review uses a systematic literature review approach. The literature used is mainly sourced through the Harzing's Publish or Perish application, considering reputable articles from 2013 to 2023 from databases such as Scopus, SAGE Journals, Taylor and Francis, Wiley, and other eligible publishers. A total of 43 articles, 3 annual reports (CATAHU) from the National Commission on Violence Against Women, and 4 books were obtained. The findings from this literature review include methods, topics, and approaches related to CDV, which are then integrated into Guidance and Counseling services.